ANALISA PEMBELIAN ALAT KESEHATAN DIMASA PANDEMI COVID-19 MELALUI PLATFORM E-COMMERCE UNTUK KONSUMEN DI KOTA BATAM - Edy Yulianto Putra; Pulung Peranginangin; Meikel Meikel (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This study aims to analyze what are the factors that cause the purchase of medical devices during the COVID-19 pandemic through several e-commerce platforms in Batam City. In this study, the sample of participants was 293 respondents who had made transactions through one of the e-commerce platforms which were distributed through online questionnaires using the judgmental sampling method and the data were processed using the Statistical Package and Service Solutions (SPSS) program. The results of this study indicate that the Hedonic Value variable has a significant effect on the Shopping Well-Being variable, while the Utilitarian Value variable has no significant effect on the Shopping Well-Being variable. Hedonic Value and Shopping Well-Being have a significant effect on the Online Purchase Intention variable, while the Utilitarian Value variable has no significant effect on the Online Purchase Intention variable. This research is expected to be a reference for some people who want to open a business on an e-commerce platform. So that it can add information and knowledge to compete with other competitors.